Avaliação in vitro do efeito das tinturas de Camellia sinensis e de Aloe arborescens na remineralização de lesão de cárie artificial em esmalte dentário humano - Salvia, Ana Carolina Rodrigues Danzi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This in vitro study evaluated the effectiveness of Camellia sinensis and Aloe arborescens tinctures in the remineralization of subsurface carious lesions artificially developed in human dental enamel. Ninety specimens from sound permanent molars were distributed into 6 groups (n=15): GH=sound enamel and artificial saliva, GS=decayed enamel and artificial saliva, GA=decayed enamel and deionized water, GF=decayed enamel and 0.05% sodium fluoride aqueous solution, GC=decayed enamel and C. sinensis tincture and GB=decayed enamel and A. arborescens tincture. Surface microhardness essay was performed on sound specimens (KHN1), after the caries lesion development (KHN2) and after treatment (KHN3). Cross-sectional microhardness essay (KHND) was performed to measure the lesion depth. One specimen of each group was submitted to: EDS to assess the enamel Ca/P ratio; SEM to verify topographical changes on the enamel surface and to the MLP to reveal the histological aspects of carious lesions. The volume percent of mineral content was performed with the KHN3 and KHND averages. The microhardness averages were submitted to the following statistical analyzes: ANOVA, Tukey multiple comparisons, Dunnettt multiple comparisons and paired t test (p<0.05). There was an increase in the surface and cross-sectional microhardness values after treatments, as well as in the mineral content, except for GA. It was concluded that the treatments were effective in remineralization of dental caries on the surface and on the cross-sectional microhardness essays, when compared to GA. All treatments reduced the depth of the lesion, especially the NaF solution, followed by C. sinensis, saliva and A. arborescens

O estudo avaliou a efetividade das tinturas de Camellia sinensis e de Aloe arborescens na remineralização de lesão artificial de cárie subsuperficial no esmalte dentário humano. Noventa espécimes de molares permanentes hígidos foram distribuídos em 6 grupos (n=15): GH=esmalte hígido e saliva artificial, GS=esmalte cariado e saliva artificial, GA=esmalte cariado e água deionizada, GF=esmalte cariado e solução aquosa de fluoreto de sódio 0,05%, GC=esmalte cariado e tintura de C. sinensis e GB=esmalte cariado e tintura de A. arborescens. A microdureza superficial foi mensurada nos espécimes quando hígidos (KHN1), após a formação da lesão de cárie (KHN2) e após os tratamentos (KHN3). A microdureza em secção transversa (KHND) foi mensurada para avaliação da profundidade da lesão. Um espécime de cada grupo foi submetido: ao EDS, para avaliar a razão Ca/P do esmalte; ao MEV, para verificar alterações topográficas na superfície e à MLP para comprovar histologicamente a formação da lesão de cárie. A porcentagem do volume de conteúdo mineral foi realizada com as médias KHN3 e KHND. As médias dos valores de microdureza foram submetidas aos testes estatísticos ANOVA, Tukey comparações múltiplas, Dunnettt comparações múltiplas e t pareado (p<0,05). Houve aumento nos valores de microdureza superficial e em secção transversa após os tratamentos, assim como do conteúdo mineral, com exceção de GA. Concluiu-se que os tratamentos foram efetivos na remineralização da lesão de cárie tanto na microdureza superficial quanto em secção transversa, quando comparados a GA. Todos os tratamentos diminuíram a profundidade da lesão, com destaque para a solução de NaF, seguido pela tintura de C. sinensis, saliva e tintura de A. arborescens
Keywords: Remineralização dentária; Flúor; Cárie dentária; Dental caries